'Some I don't remember and some I do': Memory talk in accounts of intimate partner violence. (August 2016) - Goodman, Simon; Walker, Kate
This study is the first to address the ways in which male perpetrators of intimate partner violence (IPV) talk about memory in their reports of their IPV and how these are used to manage their accountability for the violence. Drawing on and developing the discursive psychological literature on talk about memory, which highlights how such talk is used to perform practical actions within interactions, a discourse analysis is conducted on interviews with six male perpetrators of recent, multiple incidents of IPV who were undergoing treatment. The analysis identified the varying ways in which memory was used: first, claims of forgetting were used to avoid answering difficult and potentially incriminating questions; second, claims of clear memories were used to position partners as problematic and responsible for violence; and third, claims about simultaneously remembering and forgetting were found. The implications of these strategies for managing identity and accountability are discussed.